Prognostic Value of Neutrophil to Lymphocyte Ratio in Cerebral Venous Thrombosis Outcomes: Systematic Review - Ferreira, Pedro Lucas Carneiro; Vargas, Felipe Krieger; Saueressig, Lucas Vieira; Benetti, Fernando Bastiani; Neves, Letícia Poletto; Oliveira, Adilson J.M. de (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2025)
Introduction The neutrophil-to-lymphocyte ratio (NLR) is an inflammatory marker that may be associated with the presence and degree of severity of vascular diseases and is a possible predictor of risk and mortality of cerebral venous thrombosis (CVT).Methods Using PRISMA, the articles were evaluated based on sensitivity, specificity, cut-off, and AUC using the databases PUBMED and BVS. Inclusion criteria of articles were as follows: written in English, in cohort presentation, clinical trial, or control case with the key terms included in the abstract, title, or keywords of the selected articles.Results A total of 700 articles were analyzed in the databases, obtained through the search string, and evaluated for the exclusion and inclusion criteria previously indicated. Four articles were included in the final analysis. The values of sensitivity (Sen) and specificity (Esp) differed among the articles analyzed, and three of the four articles showed higher specificity. Cut-off and AUC, likewise, differed in most articles, with a lower cut-off value of 2.1 and a higher value of 6.8. The AUC ranged from 0.71–0.77. The simple mean values for Sen and Esp were 62.8% and 78.7%, respectively.Conclusion The data show that NLR can predict worse outcomes in CVT with moderate values of specificity and sensitivity (Ms Esp 78.7% / Ms Sen 62.8%).
Keywords: cerebral venous thrombosis; neutrophil-lymphocyte ratio; inflammatory marker; prognosis; predictor of risk and mortality